Nuclear Power Plants The Processes from the Cradle to the Grave - Awwad, Nasser (IntechOpen, 2021)
This book will shed light on some hot topics related to nuclear power plants starting from uranium ore processing to fabrication through enrichment and finally to nuclear fuel at nuclear reactors. This book will hopefully encourage researchers and scientists to look further into the advantages of nuclear power plants in the production of cheap electricity with low fuel cost.